2019
DOI: 10.1002/mawe.201800150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pin offset on the mechanical properties of friction stir welded AA 6013 aluminum alloy plates

Abstract: In this study, AA 6013 aluminum plates were butt‐welded with friction stir welding via pin offset technique. Macrostructural observations revealed that kissing bonds, originated from the broken oxide layers, were found to occur in the welded joints. The fracture location of welded joints after tensile tests was found to be outside the joint area, revealing that kissing bonds which were formed in the stir zone exhibited no detrimental effect on the mechanical properties of joints. Microstructural observations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Kasman and Ozan [313] studied butt FSWed joints of 6013 Al plates (Table 3) obtained via pin offset technique. The highest tensile strength equal to 206 MPa was obtained under 1.5 mm pin offset towards the advancing side and 500 min−1 TRS.…”
Section: Positioning Of Alloymentioning
confidence: 99%
See 2 more Smart Citations
“…Kasman and Ozan [313] studied butt FSWed joints of 6013 Al plates (Table 3) obtained via pin offset technique. The highest tensile strength equal to 206 MPa was obtained under 1.5 mm pin offset towards the advancing side and 500 min−1 TRS.…”
Section: Positioning Of Alloymentioning
confidence: 99%
“…Studying the butt FSWed joints of 6013 Al plates (Table 4) obtained via pin offset technique Kasman and Ozan [313] found that the highest tensile strength equal to 206 MPa was obtained under 1.5 mm pin offset towards the advancing side and 500 min −1 TRS, leading to the ratio of tensile strength of the joint to the ultimate tensile strength of the base metal (joint efficiency) equal to 74 %.…”
Section: Tool Rotation and Welding Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kasman and Ozan [355] studied butt FSW joints of 6013 Al plates (Table 4) obtained via the pin-offset technique. The highest TS, equal to 206 MPa, was obtained under the 1.5 mm pin offset toward the AS and a TRS of 500 rpm.…”
Section: Positioning Of Alloymentioning
confidence: 99%
“…Tools for friction stir welding processes consist of two essential parts, namely a pin and shoulder. The shoulder, which is a part of a tool with its higher hardness, wear resistance, and temperature durability than the material to be welded, contacts the surface of the metals to be welded; frictional heat is generated as a result of the friction between the contact surface of the tool rotation and the shoulder [16]. In addition, another component of the tool that is effective in generating heat for welding is the pin.…”
Section: Introductionmentioning
confidence: 99%